Herbaspirillum seropedicae Differentially Expressed Genes in Response to Iron Availability - María F. Trovero; Paola Scavone; Raúl Platero; Emanuel M. de Souza; Elena Fabiano; Federico Rosconi (Frontiers in Microbiology, 2018)
Herbaspirillum seropedicae Z67 is a nitrogen-fixing endophyte that colonizes many important crops. Like in almost all organisms, vital cellular processes of this endophyte are iron dependent. In order to efficiently acquire iron to fulfill its requirements, this bacterium produces the siderophores serobactins. However, the presence in its genome of many others iron acquisition genes suggests that serobactins are not the only strategy used by H. seropedicae to overcome metal deficiency. The aim of this work was to identify genes and proteins differentially expressed by cells growing in low iron conditions in order to describe H. seropedicae response to iron limitation stress. For this purpose, and by using a transcriptomic approach, we searched and identified a set of genes up-regulated when iron was scarce. One of them, Hsero_2337, codes for a TonB-dependent transporter/transducer present in the serobactins biosynthesis genomic locus, with an unknown function. Another TonB-dependent receptor, the one encoded by Hsero_1277, and an inner membrane ferrous iron permease, coded by Hsero_2720, were also detected. By using a proteomic approach focused in membrane proteins, we identified the specific receptor for iron-serobactin internalization SbtR and two non-characterized TonB-dependent receptors (coded by genes Hsero_1277 and Hsero_3255). We constructed mutants on some of the identified genes and characterized them by in vitro growth, biofilm formation, and interaction with rice plants. Characterization of mutants in gene Hsero_2337 showed that the TonB-dependent receptor coded by this gene has a regulatory role in the biosynthesis of serobactins, probably by interacting with the alternative sigma factor PfrI, coded by gene Hsero_2338. Plant colonization of the mutant strains was not affected, since the mutant strain normally colonize the root and aerial part of rice plants. These results suggest that the strategies used by H. seropedicae to acquire iron inside plants are far more diverse than the ones characterized in this work. In vivo expression studies or colonization competition experiments between the different mutant strains could help us in future works to determine the relative importance of the different iron acquisition systems in the interaction of H. seropedicae with rice plants.